Production units for primary schools - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Ndambo Ndambo, a project co-ordinator for the Zambian National Farmers Union, is concerned about the small number of school leavers who enter agriculture. He believes that setting up small production units in primary schools may be a better way of encouraging young people into agriculture than having it as a subject in the school curriculum.